2008
DOI: 10.1017/s1092852900028492
|View full text |Cite
|
Sign up to set email alerts
|

Gender-related Differences in Individuals Seeking Treatment for Kleptomania

Abstract: Objective-Understanding variations in disease presentation in men and women is clinically important as differences may reflect biological and sociocultural factors and have implications for prevention and treatment strategies. Few empirical investigations have been performed in kleptomania, particularly with respect to gender-related influences. Method-From 2001 to 2007, 95 adult subjects (n=27 [28.4%] males) with DSM-IV kleptomania were assessed on sociodemographics and clinical characteristics including symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 57 publications
1
9
0
Order By: Relevance
“…The P-K-SAS scores obtained from patients in initial treatment were consistent with those reported in other studies [27,28], confirming the suitability of this version of the K-SAS. The division of the instrument evaluation process into two parts contributed to more rigorous refinement of the instrument.…”
Section: Discussionsupporting
confidence: 88%
“…The P-K-SAS scores obtained from patients in initial treatment were consistent with those reported in other studies [27,28], confirming the suitability of this version of the K-SAS. The division of the instrument evaluation process into two parts contributed to more rigorous refinement of the instrument.…”
Section: Discussionsupporting
confidence: 88%
“…Emotional dysregulation may contribute to cravings in both behavioral and substance use disorders (8). Many people with pathological gambling, kleptomania, compulsive sexual behavior, and compulsive buying report a decrease in these positive mood effects with repeated behaviors or a need to increase the intensity of behavior to achieve the same mood effect, analogous to tolerance (911). Many people with these behavioral addictions also report a dysphoric state while abstaining from the behaviors, analogous to withdrawal.…”
Section: Introductionmentioning
confidence: 99%
“…There seems to be an interesting relationship between kleptomania and compulsive buying. Grant & Potenza (2008), in their study of 95 adults with kleptomania, found that 14.7% of the women and 11% of the men were also compulsive buyers. As already mentioned, Schlosser et al (1994) also found that kleptomania was the most common impulsecontrol disorder in compulsive buyers.…”
Section: Impulse-control Disordersmentioning
confidence: 98%